2011
DOI: 10.1016/j.jmii.2011.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of eosinophilic meningitis caused by Angiostrongylus cantonensis: 18 years’ experience in a medical center in southern Taiwan

Abstract: The epidemiology of eosinophilic meningitis has changed during the past two decades in Taiwan and occurs mainly in adults in the setting of outbreaks. Hyperesthesia; repeated lumbar puncture in cases with lymphocytic meningitis of uncertain cause; and a detailed history, including food consumption, are important to establish an accurate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 26 publications
3
38
0
4
Order By: Relevance
“…Furthermore, they also report the presence of fever (68%), hypertesia (30%), nuchal rigidity (17%), nausea and vomiting (16%), disorders of consciousness (9%), abdominal pain (9%), extraocular muscle palsy (4%) and facial palsy (1%) 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they also report the presence of fever (68%), hypertesia (30%), nuchal rigidity (17%), nausea and vomiting (16%), disorders of consciousness (9%), abdominal pain (9%), extraocular muscle palsy (4%) and facial palsy (1%) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Based , reported that no decrease in the duration of the disease was observed with the use of corticosteroids, either alone or alongside antihelminthic drugs 23 .…”
mentioning
confidence: 99%
“…Fever and malaise, though nonspecific, may also occur prior to the development of CNS disease (5). Peripheral eosinophilia was observed in 66 to 68% of cases, and CSF eosinophilia of Ն10% was noted in approximately 70 to 95% of cases (5,6). Thus, the laboratory finding of serum and especially CSF eosinophilia is an invaluable laboratory marker for A. cantonensis infection in the absence of other adjunct laboratory diagnostics.…”
mentioning
confidence: 99%
“…in rats in urban Brisbane and some surrounding areas., surpassing the two previous surveys of 123 . In fact, sero-conversion might never occur in small children 5,120 .…”
Section: Discussionmentioning
confidence: 62%
“…mackerrasae and Brazilian female A. cantonensis all showed similar degrees of recognition to the serum from human infected with A. cantonensis from Brazil (positive control), serum from experimentally infected rat and guinea pigs ( Figure 8&9). Typical signs, such as blood and CSF eosinophilia, and sero-conversion are not always present in early stages of infection 123 . In fact, sero-conversion might never occur in small children 5,120 .…”
Section: Sds-page and Western Blots Comparing The Two Angiostrongylusmentioning
confidence: 99%